Effect of precipitates on microstructural evolution of 7050 Al alloy sheet during equal channel angular rolling - Nam, CY; Han, JH; Chung, YH; Shin, MC (ELSEVIER SCIENCE SA, 2003)
Microstructural evolution during equal channel angular rolling (ECAR) is investigated in a 7050 Al alloy sheet that includes two types of precipitates, large plate-type MgZn2 and fine spherical Al3Zr. With increasing number of ECAR passes, gradual fragmentation of MgZn2 precipitates and subsequent grain refinement are revealed by transmission electron microscopy. After 6 passes of ECAR, the sheet's grain size decreases to similar to 600 nm and most large plate-type MgZn2 precipitates are fragmented into fine spherical particles. Roles of the two types of precipitates on the evolution of fine-grained structure are discussed. (C) 2002 Elsevier Science B.V. All rights reserved.